2022
DOI: 10.1136/bmjopen-2021-051953
|View full text |Cite
|
Sign up to set email alerts
|

Adverse experiences of social adaptation in children with leukaemia: a qualitative study from China

Abstract: Aim and objectiveThis study aimed to build an indepth and comprehensive understanding of the social maladaptation experience of Chinese children with leukaemia of different ages.MethodsThe purposive sampling method was adopted to conduct semistructured interviews with 20 Chinese children with leukaemia or their main caregivers and Colaizzi’s method for qualitative research was used to organise and analyse the data. The study followed the guiding principles of the Standards for Reporting Qualitative Research.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The parents in the study lived with their children in western China, including four provinces:Chongqing,Sichuan,YunnanandGuizhou.The participants were selected from the Pediatric Oncology Department of the Children's Hospital a liated to Chongqing Medical University, which is a major pediatric cancer center in western China.Based on the precisely de ned inclusion and exclusion criteria,parents of pediatric cancer patients who were hospitalized at the Children's Hospital a liated with Chongqing Medical University from August to October 2023 were meticulously chosen for this study.The process of cognitive development among children is segmented into distinct age brackets, with the age of 8 serving as a pivotal milestone. Firstly, children who have surpassed the age of 8 exhibit a brain development level that is comparable to that of adults 17 . Furthermore, research has demonstrated that these older children possess the capability to independently articulate and report their psychological sentiments 18 .For these reasons, the inclusion criteria for children with cancer were as follows: 1) The participants were diagnosed with cancer for at least 6 months based on international guidelines for the diagnosis of childhood cancer;2) age between 3 and 8 years; 3) Based on the recommended standards of the international cognitive and cancer collaborative groups for assessing cognitive impairment 19 .…”
Section: Participantsmentioning
confidence: 99%
“…The parents in the study lived with their children in western China, including four provinces:Chongqing,Sichuan,YunnanandGuizhou.The participants were selected from the Pediatric Oncology Department of the Children's Hospital a liated to Chongqing Medical University, which is a major pediatric cancer center in western China.Based on the precisely de ned inclusion and exclusion criteria,parents of pediatric cancer patients who were hospitalized at the Children's Hospital a liated with Chongqing Medical University from August to October 2023 were meticulously chosen for this study.The process of cognitive development among children is segmented into distinct age brackets, with the age of 8 serving as a pivotal milestone. Firstly, children who have surpassed the age of 8 exhibit a brain development level that is comparable to that of adults 17 . Furthermore, research has demonstrated that these older children possess the capability to independently articulate and report their psychological sentiments 18 .For these reasons, the inclusion criteria for children with cancer were as follows: 1) The participants were diagnosed with cancer for at least 6 months based on international guidelines for the diagnosis of childhood cancer;2) age between 3 and 8 years; 3) Based on the recommended standards of the international cognitive and cancer collaborative groups for assessing cognitive impairment 19 .…”
Section: Participantsmentioning
confidence: 99%